Plastidial NADP-Malic Enzymes from grasses: unravelling the way to the C4 specific isoforms - Saigo, Mariana (2013)
Malic enzyme is present in many plant cell compartments such as plastids, cytosol and mitochondria. Particularly relevant is the plastidial isoform that participates in the C4 cycle providing CO2 to RuBisCO in C4 species. This type of photosynthesis is more frequent among grasses where anatomical preconditioning would have facilitated the evolution of the C4 syndrome. In maize (C4 grass), the photosynthetic NADP dependent Malic enzyme (ZmC4-NADP-ME, L-malate:NADP oxidoreductase, E.C. 1.1.1.40) and the closest related non-photosynthetic isoform (ZmnonC4-NADPME, L-malate:NADP oxidoreductase, E.C. 1.1.1.40) are both plastidial but differ in expression pattern,kinetics and structure. Features like high catalytic efficiency, inhibition by high malate concentration at pH 7.0, redox modulation and tetramerization are characteristic of the photosynthetic NADP-ME. In this work, the proteins encoded by sorghum (C4 grass) and rice (C3 grass) NADP-ME genes,orthologues of the plastidial NADP-MEs from maize, were recombinantly expressed, purified and characterized. In a global comparison, we could identify a small group of residues which may explain the special features of C4 enzymes. Overall, the present work presents biochemical and molecular data that helps to elucidate the changes that took place in the evolution of C4 NADP-ME in grasses.